Freshmen’s Motivations and Career Objectives for Taking the Major of English Education - Sinadia, Alfrits Roul; Kondo, Petrus; Sunra, La (Journal of English Language and Education, 2024)
This study aimed to study the motivations of incoming students who decided to take the English Education Major offered by the Faculty of Education at a private university. It also sought to find out what career objectives the students plan to achieve after finishing their studies. The results of this study expectedly could become the basis for the administrators to design suitable promotional strategies to attract more incoming students. Additionally, these could help the administrators decide on strategic plans to advance and develop the best curriculum that meets the students’ expectations. The research was conducted on English Education Major students using the qualitative approach through which the data were gathered and analyzed using qualitative sampling techniques and analyses. The findings showed that most students’ motivation to take the major is to deepen their English language knowledge and develop their English skills, and some of them are truly motivated to be English teachers in the future. In terms of career objectives to achieve in the near future, most of them plan to be English teachers. Interestingly, some of them also plan for alternative careers like, for example, becoming English translators or tourist guides if they do not have the chance to be English teachers later.